Labrador, aerial view of mountains - Forbes, Alexander, 1882-1965 (1931)
(Series 15) Low altitude inland flight round Tetragona from Kangalaksiorvik to the southwest and then north to the lakes at the head of Kangalaksiorvik Fiord. Camera facing left front to line of flight. Grayscale